2020
DOI: 10.7759/cureus.6533
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Change in Microhardness by Application of MI Varnish on Primary Tooth Enamel, Affected by Use of Frequently Prescribed Paediatric Syrups: An In Vitro Study

Abstract: Open Access Original Article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
4
0
2
Order By: Relevance
“…(16) MI varnish containing CPP-ACP is a more stable and durable varnish and was found to be more effective in the reduction of Candida albicans count when compared with other fluoride varnishes Clinpro XT varnish, Fluor protector varnish, which was seen in compliance with the study conducted by Vinola Duraisamy et al (2015) (17) and Shweta Chandak et al (2016). (18) According to Salman et al (2019) (19) and Ankita Maurya et al (2020) (20) fluoride varnish containing CPP-ACP were found to have an increased acid resistance thus preventing the incidence of dental caries. This was in agreement with the current study.…”
Section: Discussionmentioning
confidence: 99%
“…(16) MI varnish containing CPP-ACP is a more stable and durable varnish and was found to be more effective in the reduction of Candida albicans count when compared with other fluoride varnishes Clinpro XT varnish, Fluor protector varnish, which was seen in compliance with the study conducted by Vinola Duraisamy et al (2015) (17) and Shweta Chandak et al (2016). (18) According to Salman et al (2019) (19) and Ankita Maurya et al (2020) (20) fluoride varnish containing CPP-ACP were found to have an increased acid resistance thus preventing the incidence of dental caries. This was in agreement with the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors like recurrent intakes (i.e., two or more times daily), sleep times, and after meals. Also, the reduced salivary flow may also promote increasing the risk of dental erosion (3,4) .…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 12 , 13 ] The severity of erosion was directly related to medicine exposure time. [ 13 14 ] Claritin™ syrup was considered in this study since it had the most erosive pattern among antihistamine-containing syrups. [ 12 ]…”
Section: Introductionmentioning
confidence: 99%